Fires in the mind : what kids can tell us about motivation and mastery - Cushman, Kathleen; What Kids Can Do (Organization) (San Francisco, CA : Jossey-Bass, 2010)
'Through the voices of students themselves, Fires in the Mind brings a game-changing question to teachers of adolescents: What does it take to get really good at something? Starting with what they already know and do well, teenagers from widely diverse backgrounds join a cutting-edge dialogue with adults about the development of mastery in and out of school. Their insights frame motivation, practice, and academic challenge in a new light that galvanizes more powerful learning for all. To put these students' ideas into practice, the book also includes practical tips for educators, exercises, questionnaires,'do' and'don't' lists, and other helpful tools'--
What does it take to get good? Young people are developing mastery in ways we easily overlook -- Catching the spark : kids tell what draws them in and gives them confidence in learning -- Keeping at it : when do young people stick with something and make it their own? -- Asking the experts : looking at how experts work, students make sense of their own process -- Exploring deliberate practice : young people look closer at what makes practice effective -- Practice and performance : demonstrating mastery also helps sutdents improve -- Bringing practice into the classroom : students imagine the classroom as a community of practice -- Is homework deliberate practice? Whether, when, and how to give kids practice after class -- School projects that build expert habits : students talk about their most compelling curricula -- Making school a community of practice : kids suggest ways that schools can foster expert habits -- Appendix A: The practice project : a five-day curriculum outline for secondary teachers or advisers : how to help students investigate the expert process -- Appendix B: Resources that help light fires in the mind : inspiration, tools, organizations, and other resources
Includes bibliographical references and index
Keywords: Mastery learning; Motivation in education; Teenagers -- Education